1998
DOI: 10.1292/jvms.60.9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of NaOH-Extracted Erysipelothrix rhusiopathiae Vaccine in Pigs.

Abstract: ABSTRACT. A vaccine was prepared from a NaOH-extracted antigen of the Kyoto strain (serovar 2) of Erysipelothrix rhusiopathiae (E. rhusiopathiae) with an oil adjuvant, and was injected twice at 3-week intervals into SPF pigs and conventional pigs with maternal antibodies. After the second vaccination, IgG-GA titers of immunized SPF pigs were more than 256-fold at 3 weeks, and immunized pigs with maternal antibodies were 64-fold at 7 weeks. The pig with maternal antibodies vaccinated once with live vaccine had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Many reports have found that the 64-to 66-kDa protein of E. rhusiopathiae is the major protective antigen (1,6,7,8,9,11,12,13,14,19). Galan and Timoney (6) are thought to have been the first to succeed in the cloning and expression of this gene from a highly virulent strain of serotype 1a; however, they did not report the gene sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have found that the 64-to 66-kDa protein of E. rhusiopathiae is the major protective antigen (1,6,7,8,9,11,12,13,14,19). Galan and Timoney (6) are thought to have been the first to succeed in the cloning and expression of this gene from a highly virulent strain of serotype 1a; however, they did not report the gene sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Various serological methods for the diagnosis of chronic swine erysipelas or for assay of maternal antibody and acquired antibody before and after vaccination have been reported, e.g., growth agglutination tests (12,20,25), the latex agglutination test (19), and enzyme-linked immunosorbent assay (ELISA) (1,2,4,9,10,11,16,17,19). Unlike in other countries, the attenuated live vaccine is the most commonly used type of vaccine in Japan, and the growth agglutination test is used for the detection of maternal antibody and acquired antibody before and after vaccination.…”
mentioning
confidence: 99%
“…In addition to pigs, E. rhusiopathiae has also been isolated from many species of both domestic and wild mammals, including humans, in which the disease is referred to as erysipeloid. 4,10 Swine erysipelas is distributed worldwide and is of economic significance. Thirty percent to 50% of pigs are known to harbor E. rhusiopathiae; however, these pigs are frequently healthy despite the presence of the organism in tonsils and lymphatic tissues.…”
mentioning
confidence: 99%
“…E. rhusiopathiae was once thought to be the only species in the genus Erysipelothrix and was classified into 25 serovars based on peptidoglycan antigens of the cell wall. At present, the genus contains at least the following two species: E. rhusiopathiae, including serovars 1a, 1b, 2,4,5,6,8,9,11,12,15,16,17,19, and 21 and type N; and Erysipelothrix tonsillarum, including serovars 3,7,10,14,20,22, and 23. Serovars 13 and 18 are unclassified but are considered to be assigned to genetically distinct groups from the above two species (15).…”
mentioning
confidence: 99%